Análise de desempenho do sistema de atendimentos de serviços em concessionária de energia - Fonini, Julio Schenato (2016)
This research presents a methodology that allows the study of the behavior of a distribution environment of work orders in electric utilities. The components in this environment have a diversity of behaviors, which complicates decision-making during the management. Considering this scenario, the problem was modeled and simulation software has been developed by integrating the stochastic behavior of its components with the deterministic routing solution already deployed on AES Sul. After the validation of the simulation process, four scenarios were created and tested in simulation application. These scenarios have changed the amount of available crews, levels of prioritization of work orders and service area segmentation. The results obtained were satisfactory both in relation to obtaining knowledge about the behavior of the system as the most appropriate formatting. The scenario that obtained the best results was completed with a low segmentation of areas and a setting that increased the level of criticality of the orders closer to the due date and who had the most relevant services.